Three-dimensional CFD simulation of oxy-fuel combustion in a circulating fluidized bed with warm flue gas recycle. (15th March 2018) - Wu, Ying; Liu, Daoyin; Duan, Lunbo; Ma, Jiliang; Xiong, Jie; Chen, Xiaoping
Highlights: CFB combustion with warm flue gas recycle is simulated. Profile of hydrodynamics, temperature and gas emission is analyzed. Combustion condition with and without warm flue gas recycle is compared. Combustion condition under a high O2 concentration is predicted. Abstract: Among various CO2 capture methods, the oxy-fuel combustion technology exhibits great potential for CO2 capture in an economical way. Based on a pilot-scale circulating fluidized bed (CFB) combustor, computational fluid dynamics (CFD) is applied to simulate the oxy-fuel CFB combustion with warm flue gas recycle (WFGR). In this work, the WFGR in the oxy-fuel CFB combustion is realized by the Eulerian-Eulerian CFD simulation. Detailed profile of the hydrodynamics, temperature, gas characteristics and pollutant emission is analyzed with good agreement between the simulated result and the experimental data achieved. Special attention is paid to the comparison of gas distribution under the combustion conditions with and without WFGR, illustrating the unique advantages of the oxy-fuel CFB combustion with WFGR in the CO2 capture and pollutant reduction. Besides, influence of the oxy atmosphere with different O2 concentrations (from 21% to 40%) on the overall performance is conducted, successfully predicting the oxy-fuel combustion with WFGR under a high O2 concentration and enriching the investigation method of the CFB combustion study.